ANALYSIS OF STRATEGY AND IMPLEMENTATION DIFFUSION OF INNOVATION OF QLUE APPLICATION TECHNOLOGY IN JAKARTA SMART CITY - Gabriella, Veronica; Hartanti, Lisa Esti Puji (School of Communication - Atma Jaya Catholic University of Indonesia, 2019)
DKI Jakarta has many challenges, so the government should be more effective and efficient to use integrated information and communication technology in every public sector, especially for the realization of a smart city program. Qlue presents as one of the innovations of communication technology to answer society’s needs of media. It is reporting all problems that happened in the neighborhood. The purpose of this research is to analyze the strategy and implementation of the diffusion of innovations that PT. Qlue Performa Indonesia has done to support the Jakarta Smart City program. This research uses qualitative methods with interviews, observation, and literature review. Then, described descriptively and analyzed with Everett Rogers’ (1983) Diffusion of Innovations theory are innovation, communication channels, time, and a social system. The result is the strategy and implementation of diffusion of innovations from Qlue need to be improved on knowledge and persuasion stage until the people of DKI Jakarta knowing about the impact of using Qlue for their daily life. In the end, the research shows that the development of the new communication technology which is more interactive has been influenced by the values of users and basic human needs.